Code halos how the digital lives of people, things, and organizations are changing the rules of business - Frank, Malcolm (John Wiley and Sons, Inc., 2014)
Harness ""Code Halos"" to gain competitive advantage in the digital era Amazon beating Borders, Netflix beating Blockbuster, Apple beating Kodak, and the rise of companies like Google, LinkedIn, and Pandora are not isolated or random events. Today's outliers in revenue growth and value creation are winning with a new set of rules. They are dominating by managing the information that surrounds people, organizations, processes, and products-what authors Malcolm Frank, Paul Roehrig, and Ben Pring call Code Halos. This is far beyond "Big Data" and analytics. Code Halos spark new co
Includes bibliographical references and index. - Print version record and CIP data provided by publisher
Keywords: Digital media -- Social aspects; Information technology -- Social aspects; Médias numériques; Aspect social; Technologie de l'information; Aspect social; SOCIAL SCIENCE; General; Digital media; Social aspects; Information technology; Social aspects